Wear modelling of a rail-wheel system - Lim, Darren Wei Xiang (Nanyang Technological University, 2020)
As one of the most efficient and aggregate means of transportation, the service life of the railway has been expected to be maintained or improved. The most important phenomenon within a rail-wheel system is the contact of rail and wheel because inappropriate interactions cause problems such as wear which will eventually lead to the reduction of the service life of the whole system. However, time-consuming and expensive experiments are generally required to study the wear of rail and wheel. Therefore, this study aims to develop a numerical multibody model to analyze and predict the wear of a rail-wheel system. A three-dimensional model has been created in Universal Mechanism based on the SMRT train car to characterize the wear performance of the rail-wheel system under different operating conditions. Simulation data has been further proceeded and analyzed through MATLAB and Microsoft Excel. The relationship between wear, velocity, equilibrium velocity, and material grade has been investigated to guide the material optimization of the current SMRT railway system. An opposing relationship between velocity equilibrium and wear of inner and outer rail has been revealed by the simulation results. Material grade R260 and R350 steel play a crucial role in terms of wear area as they differ by an average value of 8% to 9%. The development of this numerical model not only benefits our understanding of the wear mechanism within a rail-wheel system but also provides guidance on determining maintenance schedules for SMRT.